تطبيق الطريقة السمعية الشفهية في تعليم الإملاء دراسة تجريبية بمعهد دار العلوم العصري Banda Aceh - Aisyah Fadhilah; Fadhilah ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2026)
Based on initial observations made by researchers in class VII-2 at Darul Ulum Islamic Boarding School, Banda Aceh, students have not been able to write Arabic correctly, because they cannot connect and separate the letters perfectly. In the learning process, teachers do not use the right learning method, only using the lecture method. This study aims to identify student activities in the application of the Sam'iyah Syafahiyah method in Imla' Learning, and to determine the effectiveness of students in the application of Sam'iyah Syafahiyah in Imla' Learning. This research method is the One Group Pre-Test.Post, Test Design experimental method. Researchers took samples in class VII-2 totaling 21 students. The tools used in this study to collect data were observation and tests. The results of the study showed that the application of the Sam'iyah Syafahiyah Method in imla' learning was very good, as evidenced by the results of observations of student activities of 77.5%. The application of the Sam'iyah Syafahiyah Method is effective in improving students' abilities in imla' learning, with a significance level (Asymp.sig.2-tailed) of 0.000<0.05.